1986
DOI: 10.1042/bj2370913
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of an Ns-type regulatory protein in Trypanosoma cruzi membranes

Abstract: The existence of a GTP-binding protein of the Ns type in Trypanosoma cruzi was explored. Epimastigote membranes were labelled by cholera toxin in the presence of [adenine-14C]NAD+. After SDS/polyacrylamide-gel electrophoresis of extracted membrane proteins, a single labelled polypeptide band of apparent Mr approx. 45,000 was detected. Epimastigote cells were treated with N-ethylmaleimide and electrofused to lymphoma S49 cells lacking the Ns protein. Evidence indicates that in such electrofusion-generated cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…They serve as coupling units between membrane-bound receptors and effector units such as adenylate cyclase or phospholipase C. There are reports that G proteins, with characteristics similar to those of proteins known to participate in hormonally regulated signal transduction systems in higher eukaryotes, are present in T. cruzi (72). However, it has not been established that these G proteins participate in an identical manner in this parasite.…”
Section: Introductionmentioning
confidence: 99%
“…They serve as coupling units between membrane-bound receptors and effector units such as adenylate cyclase or phospholipase C. There are reports that G proteins, with characteristics similar to those of proteins known to participate in hormonally regulated signal transduction systems in higher eukaryotes, are present in T. cruzi (72). However, it has not been established that these G proteins participate in an identical manner in this parasite.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metacyclic trypomastigotes exhibit higher intracellular cyclic AMP levels than epimastigotes (13), and evidence from this laboratory has shown that T. cruzi membranes possess an adenylyl cyclase associated with the a subunit of the stimulatory guanine nucleotide-binding regulatory protein (G protein) (14). Gai and Gf3 polypeptides were also found in these membranes (15).…”
mentioning
confidence: 99%
“…The latter have been shown to be a major group of prenylated proteins in mammalian cells (6,39,40). Evidence is accumulating that Trypanosomatids contain heterotrimeric G proteins (41)(42)(43)(44)(45)(46)(47)(48), and the ␥-subunits of these signaling molecules are either geranylgeranylated (7,8) or farnesylated (49) in mammalian cells. Rab GTP-binding proteins, which are known to be doubly geranylgeranylated in mammalian cells, have recently been cloned from Trypanosomatids (50 -54).…”
mentioning
confidence: 99%